Sistem Informasi Manajemen Pengelolaan Pendapatan Asli Daerah (PAD) Berbasis Email (Studi Kasus Kabupaten Tulang Bawang- Lampung) - Sahlinal, Dwirgo; Santoso, Insap; Kadir, Abdul (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2014)
The difficulty of mobile operators signal that can be captured in the sub-districts in Tulang Bawang district, makes a problem in the data transmission process payment transactions Land and Building Tax (PBB) from business districts to the Department of Revenue Property and Public Asset (DP2KA), and need testing the type of signal that can be received in each district.This study uses data delivery technique messaging (e-mail) with software support PHP, Javascript and JSON as a form of payment transaction data to be sent. By using PHP, Javascript and JSON in this application, create an application that was developed into a platformindependent code and data both as well as low cost in implementation of e-goverenmentKeywords : PBB, DP2KA, JSON, messaging, e-goverenment